Bone health in the elderly cancer patient: A SIOG position paper. (December 2016) - Body, J.J.; Terpos, E.; Tombal, B.; Hadji, P.; Arif, A.; Young, A.; Aapro, M.; Coleman, R.
Highlights: Androgen deprivation and aromatase inhibitors increase bone loss and fracture rates. Check bone mass (DXA) at baseline and, dependent on risk, every 12–24 months. In those at increased fracture risk, antiresorptive treatment is warranted. Bisphosphonates reduce breast cancer relapse and mortality in elderly women. Bisphosphonates and denosumab delay and reduce complications of metastases. Abstract: More than a third of cancers are diagnosed in people over the age of 75. Androgen deprivation for prostate cancer and aromatase inhibitors in breast cancer accelerate age-related bone loss and increase fracture rates. BMD should be checked by dual energy X-ray absorptiometry at baseline and, dependent on risk, every 12–24 months. Sufficient calcium, vitamin D and exercise are part of primary fracture prevention. Resistance exercise in particular may improve functional activity and bone density. In men at increased fracture risk and women with postmenopausal early breast cancer, antiresorptive treatment is warranted to reduce fracture rate and to increase overall survival in breast cancer. Bone metastases (BM) are common in breast and prostate cancer and lytic bone lesions typical of multiple myeloma. They can cause fractures, pain and spinal cord compression, require surgery or radiation for symptom relief, and lead to hypercalcaemia. Multidisciplinary working with patients and carers can improve quality of life for elderly patients with BM and mitigate the adverse consequences of therapy. Bisphosphonates and other osteoclast inhibitors such as denosumab reduce this morbidity, improve quality of life and reduce pain. Especially in the elderly, attention should be paid to renal function and to risk factors for osteonecrosis with bone-modifying agents. Attention should also be paid to hypocalcaemia risk, which can be considerable in elderly men with metastatic prostate cancer and vitamin D deficiency. We urgently need further research specifically directed at assessing risks and benefits of bone targeted treatments in the growing population of elderly cancer patients.